Malignancy and mortality in paediatric‐onset inflammatory bowel disease: a 3‐year prospective, multinational study from the paediatric IBD Porto group of ESPGHAN. Issue 5 (8th July 2018) - Joosse, M. E.; Aardoom, M. A.; Kemos, P.; Turner, D.; Wilson, D. C.; Koletzko, S.; Martin‐de‐Carpi, J.; Fagerberg, U. L.; Spray, C.; Tzivinikos, C.; Sladek, M.; Shaoul, R.; et al.
Summary: Background: Risk benefit strategies in managing inflammatory bowel diseases (IBD) are dependent upon understanding the risks of uncontrolled inflammation vs those of treatments. Malignancy and mortality in IBD have been associated with disease‐related inflammation and immune suppression, but data are limited due to their rare occurrence. Aim: To identify and describe the most common causes of mortality, types of cancer and previous or current therapy among children and young adults with paediatric‐onset IBD. Methods: Information on paediatric‐onset IBD patients diagnosed with malignancy or mortality was prospectively collected via a survey in 25 countries over a 42‐month period. Patients were included if death or malignancy occurred after IBD diagnosis but before the age of 26 years. Results: In total, 60 patients were identified including 43 malignancies and 26 fatal cases (9 due to cancer). Main causes of fatality were malignancies (n = 9), IBD or IBD‐therapy related nonmalignant causes (n = 10; including 5 infections), and suicides (n = 3). Three cases, all fatal, of hepatosplenic T‐cell lymphoma were identified, all were biologic‐naïve but thiopurine‐exposed. No other haematological malignancies were fatal. The 6 other fatal cancer cases included 3 colorectal adenocarcinomas and 3 cholangiocarcinomas (CCAs). Primary sclerosing cholangitis (PSC) was present in 5 (56%) fatal cancers (1 colorectal carcinoma, 3 CCAs and 1 hepatosplenic T‐cell lymphoma). Conclusions: We report the largest number of paediatric‐onset IBD patients with cancer and/or fatal outcomes to date. Malignancies followed by infections were the major causes of mortality. We identified PSC as a significant risk factor for cancer‐associated mortality. Disease‐related adenocarcinomas were a commoner cause of death than lymphomas.